HUBUNGAN DEMOGRAFI DENGAN LAMA PENGALAMAN INVESTASI SEORANG INVESTOR DI KOTA SURABAYA - Wong, Sharon; Jocelyn, Angelique; Mintarja, Natasya (Jurnal Manajemen, 2024)
The primary aim of this study is to analyze the relationship between demographic factors and the investment experience of stock investors. Specifically, it explores how factors such as gender, age, educational level, income level and occupation are related to the duration of an investor’s experience in the stock market. This study is quantitative and employs a purposive sampling technique, focusing on stock investors in Surabaya City with a sample size of 110 respondents. Data was collected through a questionnaire created on Google Forms. The data acquired was analyzed using SPSS Version 29 software, employing two statistical tests, Chi-Square test and ANOVA. The Chi-Square test was used to examine the relationships between demographic factors - gender, age, occupation, educational level and income level - are significantly related to an investor’s investment experience. Based on the ANOVA test, which was used to compare differences, it is shown that only gender had a significant impact on investment experience.